Smart Folding and Floating Shelter Design for Disaster Mitigation with Natural Ventilation and UVC System - Alfian, Ndaru Nuridho; Kartikasari, Damara; Widodo, Nur Setyo Adi; Suroso, Dwi Joko (TDMRC, Universitas Syiah Kuala, 2021)
The global COVID-19 outbreak has hit the world in the last two years. Indonesia itself recorded positive cases of COVID-19 of approximately 4 million cases as of September 15, 2021. In addition, the frequency of occurrence of natural disasters in Indonesia, which is relatively high every year, requires our collective attention. In early 2021, there have been several natural disasters, including floods in South Kalimantan, earthquakes in West Sulawesi, and others. If the impact of the natural disaster makes residents must do the evacuation, a proper shelter (evacuee camp) and prioritizes health protocols are needed. Therefore, this study discusses the design innovation of disaster response shelters in the form of smart folding and floating shelters designed for a shelter with a capacity of one family (4-5 people). This capacity limitation is to maintain health protocols and suppress the transmission of the Coronavirus in evacuation areas. Our designed shelter prepared in a compact form to facilitate evacuation mobility and can be implemented in all types of disasters with a folding and floating structure system (the shelter can float and be folded). The material used is light steel as the main structure and cork wall as a material that allows the shelter to float. We designed natural ventilation to regulate air circulation, integrated with an ultraviolet C (UVC) lamp. The UVC lamp is intended as a disinfectant against the Coronavirus. Thus, the application of natural ventilation and disinfection using UVC can provide a cleaner air supply. This air supply and circulation are shown in our simulation results using ANSYS Fluent. These results show that smart folding and floating shelter designs can be used for disaster mitigation.